Pelatihan Napas "Tiup API" Untuk Proses Persalinan Kala I - -, Ari Sulistyawati (ABDIMAS Madani, 2022)
First stage of labor is the longest stage of the entire labor process. Contraction pain in the first stage is the most burdensome thing for mothers in labor. Not infrequently, in the middle of the delivery process a mother prefers to give up and decides to give birth. Actually, the first stage with painful contractions can be passed by using proper breathing techniques, but not all maternity mothers understand and are able to apply it. This community service activity aims to provide knowledge and skills for pregnant women using the “blowing fire” breathing technique during the first stage of labor. The method used in this activity is education about breathing techniques used during delivery to pregnant women who are members of the WhatsApp group My Amazing Delivery and MomID . Education is carried out in a classical form, consisting of the delivery of material followed by questions and answers. This activity was held on 9-15 June 2022 attended by 277 people. The results of the activity showed an increase in knowledge and skills of pregnant women in doing self-suggestion and breathing exercises with the "blowing fire" technique which was originally 31.2% (75 people) in the category of moderately increasing in being good. Meanwhile, 68.8% of participants (159 people) who previously did not know and only knew a little about self-suggestion and breathing techniques increased in the sufficient category. The participants also said that their confidence in facing labor increased because they felt they had ammunition to face the most thrilling moment, namely contractions. It is expected that pregnant women can access information related to preparation for childbirth so that they have positive self-confidence in facing childbirth.